Getting Ready for the Hydrogen Evolution Reaction: The Infrared Spectrum of Hydrated Aluminum Hydride–Hydroxide HAlOH+(H2O)n−1, n=9–14. Issue 31 (4th June 2021) - Heller, Jakob; Tang, Wai Kit; Cunningham, Ethan M.; Demissie, Ephrem G.; van der Linde, Christian; Lam, Wing Ka; Ončák, Milan; Siu, Chi‐Kit; Beyer, Martin K.
Abstract: Hydrated singly charged aluminum ions eliminate molecular hydrogen in a size regime from 11 to 24 water molecules. Here we probe the structure of HAlOH + (H2 O)n−1, n=9–14, by infrared multiple photon spectroscopy in the region of 1400–2250 cm −1 . Based on quantum chemical calculations, we assign the features at 1940 cm −1 and 1850 cm −1 to the Al−H stretch in five‐ and six‐coordinate aluminum(III) complexes, respectively. Hydrogen bonding towards the hydride is observed, starting at n=12. The frequency of the Al−H stretch is very sensitive to the structure of the hydrogen bonding network, and the large number of isomers leads to significant broadening and red‐shifting of the absorption of the hydrogen‐bonded Al−H stretch. The hydride can even act as a double hydrogen bond acceptor, shifting the Al−H stretch to frequencies below those of the water bending mode. The onset of hydrogen bonding and disappearance of the free Al−H stretch coincides with the onset of hydrogen evolution. Abstract : Water molecules must arrange around an aluminum hydride–hydroxide unit in a specific way to enable elimination of molecular hydrogen. Infrared multiple photon dissociation spectroscopy reveals that hydrogen bonding to the hydride takes place in a six‐coordinate Al III hydride–hydroxide complex. The smallest cluster size for which hydride hydrogen bonding dominates is also the cluster size for which hydrogen evolution becomes efficient.